2024
DOI: 10.1021/acsaenm.4c00232
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-Enriched Carbon Aerogels Derived from Polybenzoxazine Cross-Linked Graphene Oxide-Chitosan Hybrid Matrix with Superior CO2 Capture Performance

Almahdi A. Alhwaige,
Hatsuo Ishida,
Syed A. Qutubuddin

Abstract: The present study reports advanced nitrogen-enriched carbon aerogels (N-CAs) that have been derived from the pyrolysis of polybenzoxazine cross-linked graphene oxide-chitosan aerogels. The role of the BZ chemical structure and the impact of KOH chemical activation of the obtained N-CAs on the BET specific surface area, porosity characteristics, and CO 2 adsorption capacity have been studied. The impact of the molecular structure of benzoxazine precursors on the CO 2 adsorption behavior has been investigated us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…Consequently, MCs are widely considered as excellent electrode materials for supercapacitors, demonstrating outstanding performance . PBZs also exhibit great potential for high-performance nitrogen-doped MCs due to their robust heat stability, high char yield, robust heat stability, and less shrinkage. , Moreover, the nitrogen (N) content in these materials could be modified by adjusting the amine percentage in the PBZs structure . Wan et al revealed that NPMCs with high O and N contents derived from BZ with CN groups showed a maximum capacitance of 362.4 F g –1 , along with an impressive retention rate of 94.7% …”
Section: Introductionmentioning
confidence: 99%
“…Consequently, MCs are widely considered as excellent electrode materials for supercapacitors, demonstrating outstanding performance . PBZs also exhibit great potential for high-performance nitrogen-doped MCs due to their robust heat stability, high char yield, robust heat stability, and less shrinkage. , Moreover, the nitrogen (N) content in these materials could be modified by adjusting the amine percentage in the PBZs structure . Wan et al revealed that NPMCs with high O and N contents derived from BZ with CN groups showed a maximum capacitance of 362.4 F g –1 , along with an impressive retention rate of 94.7% …”
Section: Introductionmentioning
confidence: 99%